(untitled) (Journal of the College of Basic Education, 2022)
The study included the internal structure of the root and recognition of the tissue constituent and the varies in the thickness of the cortex, the shape of the central cylinder, the number of xylem arches, es, and the existence or absence of crystals. The cross-section of stems showed taxonomical characteristics like the shape of the cross-section and thickness of the epidermis, sclerenchyma, chlorenchyma, and parenchyma also the distribution of vascular bundles this helped distinguish between the two types under study and noting the importance of the anatomical characteristics, The study showed results and characters and these were present for the first time investigation include plates of sections which studied in addition to tables.